Thermal insulation and mechanical properties of construction materials with nitrile rubber (NBR) waste for construction industry - Othman, Rafidah (2007)
Rubber waste is one of waste materials listed in the ‘First Schedule’ of scheduled waste list in Environmental Quality Regulation 2005 (Scheduled Waste). Scheduled wastes are normally associated with tight management and high cost of disposal. Conventionally, they are incinerated in combustion system with gases effluent treatment system. This research was aimed to investigate the effects of adding nitrile rubber (NBR) waste on the mechanical properties and thermal conductivity of clay bricks. For this investigation, mechanical tests; compression strength test and water absorption test were carried out on the samples of clay bricks impregnated with NBR waste. Samples used in this research were produced by compacting and extruding the mixture into the required size before being fired in an oven at 1060°C for ten hours.1.5 pphr of NBR waste was introduced into the standard mixture of clay bricks. Sodium silicate was used as stabilizer in both mixtures. It was observed that NBR waste-clay bricks performed higher percentage of water absorption while showed slight lower compressive strength than the standard bricks. NBR waste was found to improve the insulation property of clay bricks.